1993
DOI: 10.1007/bf01153676
|View full text |Cite
|
Sign up to set email alerts
|

The temporal organization of the correlational association of neurons of the cat motor cortex

Abstract: The multineuronal activity was recorded in cats with a developed conditioned food-procuring reflex to time. Cross-correlation histograms were plotted on the basis of the impulse activity of individual neurons isolated from the multineuronal activity, and an analysis was made of the distribution in real time of the impulses constituting the peaks on these histograms. The secondary analysis of the histograms made it possible to identify the dynamics of the changes in the functional connections between neurons ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…Of 45 neuron pairs recorded in four experiments, 12 pairs (26.6%) showed increases in the frequency of linked spike activity at the moment of presentation of the conditioned stimulus; for several pairs, this increase in frequency was demonstrated in two to four fragments of a single experiment. In two cats in which CRT was developed, of 38 neuron pairs recorded in six experiments, increases in the frequency of linked spike activity at the point at which the conditioned reflex interval ended were seen in nearly one third of cases -46% in one animal and 24% in the other [4]. Neuronal activity in these animals was analyzed only for the second half of the conditioned reflex interval (the active waiting (AW) phase), since the aim of these studies was to identify changes occurring at the level of interneuron interactions with the animals' behavior.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Of 45 neuron pairs recorded in four experiments, 12 pairs (26.6%) showed increases in the frequency of linked spike activity at the moment of presentation of the conditioned stimulus; for several pairs, this increase in frequency was demonstrated in two to four fragments of a single experiment. In two cats in which CRT was developed, of 38 neuron pairs recorded in six experiments, increases in the frequency of linked spike activity at the point at which the conditioned reflex interval ended were seen in nearly one third of cases -46% in one animal and 24% in the other [4]. Neuronal activity in these animals was analyzed only for the second half of the conditioned reflex interval (the active waiting (AW) phase), since the aim of these studies was to identify changes occurring at the level of interneuron interactions with the animals' behavior.…”
Section: Resultsmentioning
confidence: 94%
“…In this report we present only a number of fragments of these experiments, which were not included in the previous report [4], but which are very important primarily because they allowed us to consider the distribution of linked spikes at the earliest stages of the experiment. Figure 2 shows the dynamics of linked spikes and the distribution of spikes of initial spike trains on the first day of the experiment involving training to the CRT in previously untrained cats.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The very first analysis of linked spike activity, in the cat motor cortex [4,10], performed in real time, showed that the interval between linked spikes could vary over a wide range, lasting from several milliseconds to several seconds. Subsequent studies established [3] that linked spike activity is an independent process based on spontaneous spike discharges but differing from these in terms of its involvement in particular physiological functions. Linked spikes from some pairs of neurons…”
mentioning
confidence: 97%